The antiracist kid : a book about identity, justice, and activism - Jewell, Tiffany (Versify : HarperCollins Publishers, 2022)
Presents a young person's guide to terms associated with identity, social justice movements, and activism. Answers questions about racism, biases, power, oppression, ageism, cissexism, classism, and microaggressions. Discusses what it means to be antiracist, and offers suggestions for attending protests, making signs, writing letters, and resisting racism at home, school, and in the community. Includes fact boxes, critical thinking questions, a glossary of terms, and booklists for children and adults.